RESPON PUBLIK TERHADAP FATWA BOIKOT PRODUK ISRAEL OLEH MAJELIS ULAMA INDONESIA - Prihandono Wibowo; Renitha Dwi Hapsari; Muchammad Chasif Ascha (Halu Oleo University, 2024)
Israel's aggression against Gaza since October 2023 has sparked global support for Palestine. One of the supports was shown by the Indonesian Ulema Council by issuing fatwa number 83 of 2023. One of the points of the fatwa is to avoid transactions and not use products affiliated with Israel. This fatwa is identified with the boycott of Israeli products. This paper attempts to analyze the public response to the MUI fatwa. The method used in this research is Discourse Network Analysis (DNA). This research uses DNA Analyzer and Visone software to display actor and discourse networks and statistical calculations of actors and discourses responding to Fatwa number 83 of 2023. The research measured public response for one month since the fatwa was issued on November 8, 2023. The findings in this study are that the public is divided into 2 clusters in responding to the fatwa. The first cluster expressed support, and the second cluster expressed disapproval of the fatwa. However, the analysis and statistical calculations found that actors and discourses that support the MUI fatwa are more dominant. From the results of analysis and statistical calculations, it was found that actors and discourses that support the MUI fatwa are more dominant.